“Nonisocyanate” polyhydroxy urethanes based on the raw material of a plant origin - Karateev, Arnold; Litvinov, Denis; Kalkamanova, Olesya (Publishing House of Lviv Polytechnic National University, 2014)
New furfuryl oxypropyl cyclocarbonate (FOPCC)-based “nonisocyanate” polyhydroxy urethanes (PHU) (FOPCC being a product of recycled renewable raw materials) have been synthesized. The urethane formation reaction was investigated using infrared spectroscopy. The method of differential scanning calorimetry was used for the studies of the kinetics of reactions that form PHU, in particular the urethane-formation reaction and Diels-Alder reaction. It has been shown that FOPCC derivatives can be polymerized in the presence of a complex onium catalyst. Thermally reversible and thermally irreversible cross-linked PHUs have been produced. Cинтезовано нові “неізоціанатні” полігід- роксиуретани (ПГУ) на основі фурфурилоксипропілциклокарбонату (ФОПЦК) – продукту перероблення відновлюваної сировини. Методом інфрачервоної спектроскопії досліджено реакцію уретаноутворення. Методом диференційно-скануючої калориметрії вивчена кінетика реакцій утворення ПГУ: реакція уретаноутворення і реакція Дільса-Альдера. Показана можливість полімеризації похідних ФОПЦК у присутності комплексного онієвого каталізатора. Одержано як термооборотні, так і термонеоборотні сітчасті ПГУ.
"Неізоціанатні" полігідроксиуретани на основі сировини рослинного походження
Keywords: nonisocyanate polyhydroxy urethanes; renewable raw material; furfuryloxypropyl cyclocarbonates; Diels-Alder reaction; неізоціанатні полігідроксиуретани; відновлювальна сировина; фурфурилоксипропілциклокарбонат; реакція уретаноутворення; реакція Дільса-Альдера